2021
DOI: 10.1021/acsanm.1c01743
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Magnesium Ferrite Nanoparticles for Selective and Sustainable Remediation of Congo Red

Abstract: Surface modification of silica-coated magnesium ferrite nanoparticles (MgFe 2 O 4 @SiO 2 NPs) by 3-aminopropyltriethoxysilane (APTES) shows enhanced selectivity for the removal of Congo Red (CR) from both single and binary aqueous dye solutions. Before coating the surfaces of amine-functionalized magnesium ferrite nanoparticles (MgFe 2 O 4 −NH 2 NPs) with silica, control studies of the adsorption of cationic, neutral, and anionic dyes were performed using both single and binary dye systems. The studies found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…These findings indicated that the adsorption of IC and MB by the unmodified MgFe 2 O 4 NPs was independent of pH. In addition, the MgFe 2 O 4 nanoadsorbent preferentially adsorbed the anionic IC dye rather than the cationic MB dye, as observed in a previous study . The efficiency for removal of IC by the MgFe 2 O 4 /PCysMA nanoadsorbent decreased from ∼95 to ∼10% upon increasing the solution pH from ∼2 to ∼10.…”
Section: Results and Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These findings indicated that the adsorption of IC and MB by the unmodified MgFe 2 O 4 NPs was independent of pH. In addition, the MgFe 2 O 4 nanoadsorbent preferentially adsorbed the anionic IC dye rather than the cationic MB dye, as observed in a previous study . The efficiency for removal of IC by the MgFe 2 O 4 /PCysMA nanoadsorbent decreased from ∼95 to ∼10% upon increasing the solution pH from ∼2 to ∼10.…”
Section: Results and Discussionsupporting
confidence: 77%
“…In addition, the MgFe 2 O 4 nanoadsorbent preferentially adsorbed the anionic IC dye rather than the cationic MB dye, as observed in a previous study. 56 The efficiency for removal of IC by the MgFe 2 O 4 /PCysMA nanoadsorbent decreased from The efficiencies for removal of IC and MB by the MgFe 2 O 4 @SiO 2 and MgFe 2 O 4 @SiO 2 /PCysMA nanoadsorbents were also studied to investigate pH-dependent adsorption by the PCysMA-grafted nanoadsorbent, and the results are presented in Figure 6b. At pH ∼2, the MgFe 2 O 4 @SiO 2 nanoadsorbent provided ∼44% IC removal efficiency, whereas no adsorption of IC occurred upon increasing the solution pH from ∼4 to ∼10.…”
Section: Characterization Ofmentioning
confidence: 99%
“…According to the literature, the mechanism of dye adsorption may be through host–guest interactions, particularly those involving electrostatic interactions, hydrogen bonding, or π–π stacking. 53,54 Furthermore, the zeta potentials of complexes 1 and C-N-1 were measured and found to be 0.0207 and 0.0813 mV, respectively (Fig. S10†), which suggested that electrostatic interactions may have been the main mechanism through which the dye adsorption was achieved.…”
Section: Resultsmentioning
confidence: 97%
“…The MgFe 2 O 4 nanoparticles were synthesized according to our previous reports. ,, Briefly, CH 3 COONa (15 mmol) was mixed with 10 mL of ethylene glycol followed by heating to 100 °C for 15 min. Mg­(NO 3 ) 2 ·6H 2 O (1 mmol), Fe­(NO 3 ) 3 ·9H 2 O (2 mmol), and 5.0 mL of ethylene glycol were injected into the reaction mixture and subsequently refluxed for 30 min.…”
Section: Methodsmentioning
confidence: 99%